Superb microvascular imaging ultrasound of the knee in patients with juvenile idiopathic arthritis—a repeatability study - Dohna, Martha; Gohar, Faekah; Neuhäuser, Markus; Franke, Doris; Memaran, Nima; Raab, Anna; Drube, Jens; Dressler, Frank; Windschall, Daniel (Frontiers in Pediatrics, 2026)
IntroductionJuvenile idiopathic arthritis (JIA) is the commonest rheumatologic disease in children and frequently affects the knee joint. Synovial inflammation and tenosynovitis are key pathological features, and ultrasound plays an increasingly important role in their assessment. Superb Microvascular Imaging (SMI) is a novel Doppler technique with enhanced sensitivity to low-velocity microvascular flow, but evidence on its repeatability in JIA remains limited. This study aimed to evaluate intra- and inter-observer repeatability of knee SMI in children with JIA.MethodsIn this prospective multicenter study (June 2023–October 2024), 76 children with JIA were examined (Hannover Medical School and St. Josef-Stift Sendenhorst). Each underwent three standardized SMI scans: two by the same and one by a different examiner. Synovial vascularity was graded using the Pediatric OMERACT scoring system. Intra- and inter-observer reliability measures were calculated using intra-class correlation coefficients (ICC). Agreement between longitudinal and transverse suprapatellar planes was assessed using weighted kappa statistics, and correlations with clinical disease activity were analyzed via logistic regression.ResultsIntra-observer reliability was excellent (ICC = 0.972, 95% CI: 0.956–0.982). Inter-observer reliability was strong (ICC = 0.828–0.928), regardless of examiner experience. Agreement between imaging planes was substantial (κ = 0.72, p = 0.32). Synovial vascularity scores correlated significantly with clinical measures of active arthritis (OR = 1.182, p = 0.0004), particularly with swelling (OR = 1.249, p < 0.0001).DiscussionSMI demonstrates excellent repeatability for assessing synovial vascularity in JIA. Its reliability, examiner independence, and non-invasive nature support its use for routine monitoring and longitudinal disease evaluation in pediatric rheumatology.